2009
DOI: 10.1029/2008gc002348
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of plate bending at the trench and slab‐plate coupling

Abstract: [1] The bending strength of subducting lithosphere plays a critical role in the Earth's plate tectonics and mantle convection, modulating the amount of slab pull transmitted to the surface and setting the boundary conditions under which plates move and deform. However, it is the subject of a lively debate how much of the potential energy of the downgoing plate is consumed in bending the plate and how the lithospheric strength is defined during this process. We model the subduction of a viscoelastic lithosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
119
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 61 publications
(146 reference statements)
16
119
2
Order By: Relevance
“…This would indicate that in nature less than 1% of the slab's potential energy is dissipated in the slab during plan view curvature. As shown in recent laboratory and numerical experiments of Earth‐like subduction settings, most of the potential energy of the slab is dissipated in the ambient mantle, while a relatively small percentage (<20%) is dissipated in the hinge of the subducting plate [ Stegman et al , 2006; Capitanio et al , 2007, 2009; Krien and Fleitout , 2008; Schellart , 2009]. Note, however, that other recent work argues that ∼45% is dissipated in the plate during subduction [ Di Giuseppe et al , 2008].…”
Section: Discussionmentioning
confidence: 99%
“…This would indicate that in nature less than 1% of the slab's potential energy is dissipated in the slab during plan view curvature. As shown in recent laboratory and numerical experiments of Earth‐like subduction settings, most of the potential energy of the slab is dissipated in the ambient mantle, while a relatively small percentage (<20%) is dissipated in the hinge of the subducting plate [ Stegman et al , 2006; Capitanio et al , 2007, 2009; Krien and Fleitout , 2008; Schellart , 2009]. Note, however, that other recent work argues that ∼45% is dissipated in the plate during subduction [ Di Giuseppe et al , 2008].…”
Section: Discussionmentioning
confidence: 99%
“…7.3. However Korenaga's model depends on assuming a small and unchanging radius of curvature of bending plates, and this is not supported by current observations (Wu et al, 2008) nor by recent modelling that indicates the radius of curvature will be larger for thicker plates (Capitanio et al, 2009). If even modestly more plausible radii of curvature are assumed the recent thermal history reverts to being close to previous conventional histories (Davies, 2009a) and the reconciliation with cosmochemical estimates is lost.…”
Section: Cosmochemical Abundances and Thermal Evolutionmentioning
confidence: 92%
“…The weak crust has a lower yield strength than the underlying material and accommodates the plastic deformation of the bending plate (Capitanio et al, 2009). Using a different model setup, found that the combination of sticky air and weak crust promotes 1-sided subduction.…”
Section: The Surfacementioning
confidence: 99%